Effects of Broad-Spectrum Antimicrobials on Patients with Community-Acquired Pneumonia with Low Risk for Drug-Resistant Pathogens: Historical Cohort Study in Japan - Takahiro Takazono; Naoki Hosogaya; Yoshiyuki Saito; Masahiko Takemura; Naoki Iwanaga; Noriho Sakamoto; Junichi Hirayama; Rie Ueno; Hiroshi Mukae (Infectious Diseases and Therapy)
Abstract Introduction Broad-spectrum antimicrobials are commonly administered for community-acquired pneumonia (CAP); however, unnecessary administration may cause adverse events and poor outcomes. This study aimed to understand the impact of broad-spectrum anti-pseudomonal β-lactam use on clinical outcomes and healthcare resource utilization (HCRU) in inpatients with CAP and a low risk of drug-resistant pathogens (DRPs). Methods This historical cohort study reviewed Japan’s hospital claims database (January to December of 2018) and included inpatients aged ≥ 20 years who received intravenous antimicrobial therapy for CAP. Those with high DRP risk were excluded. According to the initial antimicrobial regimen, patients were divided into broad-spectrum (anti-pseudomonal β-lactam therapy) and narrow-spectrum (non-anti-pseudomonal β-lactam therapy) groups. This study evaluated 30-day hospital mortality as a primary outcome using inverse probability of treatment weighting (IPTW) to adjust for differences between both groups and HCRU as an exploratory analysis. Results A total of 15,617 patients were analyzed (2627 in the broad-spectrum group and 12,990 in the narrow-spectrum group). In the broad-spectrum group, the 30-day mortality rate was 10.6%, which was higher than that in the narrow-spectrum group (5.3%). Furthermore, it was associated with an increased 30-day mortality compared with the narrow-spectrum group after IPTW (adjusted odds ratio, 1.77; 95% confidence interval, 1.52–2.06; p < 0.001). The mean inpatient cost was USD 6139 and USD 5184 for the broad- and narrow-spectrum groups, respectively. Conclusions The initial use of anti-pseudomonal β-lactams for CAP with low DRP risk is associated with poor outcomes, including death and high HCRU. Thus, initial antimicrobials should be judiciously selected for CAP management.